Roseburia hominis improves host metabolism in diet-induced obesity - Wenli Huang; Wenyi Zhu; Yu Lin; Francis K. L. Chan; Zhilu Xu; Siew C. Ng (Gut Microbes)
Next-generation live biotherapeutics are promising to aid the treatment of obesity and metabolic diseases. Here, we reported a novel anti-obesity probiotic candidate, Roseburia hominis, that was depleted in stool samples of obese subjects compared with lean controls, and its abundance was negatively correlated with body mass index and serum triglycerides. Supplementation of R. hominis prevented body weight gain and disorders of glucose and lipid metabolism, prevented fatty liver, inhibited white adipose tissue expansion and brown adipose tissue whitening in mice fed with high-fat diet, and boosted the abundance of lean-related species. The effects of R. hominis could be partially attributed to the production of nicotinamide riboside and upregulation of the Sirtuin1/mTOR signaling pathway. These results indicated that R. hominis is a promising candidate for the development of next-generation live biotherapeutics for the prevention of obesity and metabolic diseases.